2018
DOI: 10.1108/er-06-2017-0134
|View full text |Cite
|
Sign up to set email alerts
|

Engaging employees with disabilities in Vietnamese business context

Tuan Trong Luu

Abstract: Purpose There has been a growing number, though still modest, of organizations in Vietnam context that hire employees with disabilities and build disability inclusive management practices and disability diversity climate for them to engage in their work roles. The purpose of this paper is to investigate how disability inclusive HR practices contribute to work engagement of employees with disabilities working in Vietnam-based information technology (IT) industry. Design/methodology/approach The research model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 103 publications
1
17
0
Order By: Relevance
“…In addition, the results showed that the interactive effects of F I G U R E 3 Three-way interactive effect on employee performance future research (Aguinis & Glavas, 2019). Therefore, GHRM plays an essential role in supporting and implementing CSR policies in hotels, and this is consistent with the perspectives of Luu (2018) and Y. J. Kim et al (2019).…”
Section: Modelsupporting
confidence: 61%
“…In addition, the results showed that the interactive effects of F I G U R E 3 Three-way interactive effect on employee performance future research (Aguinis & Glavas, 2019). Therefore, GHRM plays an essential role in supporting and implementing CSR policies in hotels, and this is consistent with the perspectives of Luu (2018) and Y. J. Kim et al (2019).…”
Section: Modelsupporting
confidence: 61%
“…Our first contribution pertains to providing a more nuanced and less obvious consideration of human capital that resides in a specific category of neurodivergent people. While we observe a tendency in research to move away from focusing on privileged workers as organizational assets (Ashley and Empson, 2013) to acknowledge the contribution of disabled employees to organizational success (Luu, 2018), little is still known about the value of neurodivergent human capital. We therefore contribute to the emerging strength-based approach to mental disorders (Wiklund et al , 2020) and neurodiversity (Wiklund et al , 2018) where a focus is placed on a person's assets as opposed to weaknesses.…”
Section: Discussionmentioning
confidence: 98%
“…The 38 articles that were included in the review applied different methodologies: 18 articles described quantitative studies [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], 16 articles described qualitative studies [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] and four studies applied mixed methods [89][90][91][92]. An overview of the articles, structured by methodology and listed from highest quality to lowest quality, can be found in Tables 1, 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, developing a strategic plan to normalise disability was found to be positively related to labour inclusion of persons with disabilities [68]. Lastly, moving beyond solely promoting senior management's commitment, openly addressing stigma within the organisation was valued [64,78].…”
Section: Senior Management Commitmentmentioning
confidence: 99%
See 1 more Smart Citation